SISTEM MONITOR BUDI DAYA SARANG BURUNG WALET BERBASIS ESP32-CAM DILENGKAPI APLIKASI TELEGRAM - Maulana, Dani; Raka Agung, I Gusti Agung Putu; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i01.p17, 2022)
Swiftlet nest farming is one of the businesses found in Indonesia due to its big economic value. Nest quality at the time when harvest is able to impact the selling price of swiftlet nest. Farmers usually monitor the swiftlet nest by checking the nest directly in the building, this matters because the swiftlet is shocked. Monitoring is needed for checking the physical condition of the swiftlet nest. This research will make a prototype hopefully useful to swiftlet nest farmers as a reference to increase nest quality with high economic value. The research has been done on software and hardware design by ESP32-CAM and Arduino IDE software for making the source code. The result from research of a monitoring system on swiftlet nest farming based ESP32-CAM equipped with telegram is able to send commands menu to telegram, capturing photo of swiftlet nest, turning on flash and turning off flash on ESP32-CAM. The research has been realized successfully as design.